Injuries to young professional baseball pitchers cannot be prevented solely by restricting number of innings pitched - Karakolis, T.; Bhan, S.; Crotin, R. L. (The Journal of Sports Medicine and Physical Fitness, 2016)
BACKGROUND: The Major League Baseball schedule is longer and more intensive than minor and amateur leagues. As a result, major league pitchers endure a considerably higher cumulative workload throughout the season. Ligament, tendon, muscle, and bone tissues in young pitchers need time to adapt to the workload a major league pitcher must endure. To mitigate the risk of overuse injury, and allow time for tissue adaptation to occur, most teams limit the number of innings a young pitcher may throw. This study examined the relationship between innings pitched and future injury in young professional baseball pitchers.